Peran Karakteristik Ibu yang Berpengaruh Terhadap Kasus Maternal Dental Anxiety Di Masa Pandemi Covid-19 - Dien, Sinta Nuriyah; Chandana, Rizka Nastasia Chandana; Putri, Vaira Azlia Vrilly; Sabdho Wening, Gilang Rasuna (Poltekkes Kemenkes Kendari, 2023)
Maternal dental anxiety is an emotional response to dental and oral care that cannot be explained by the mother, and can affect the level of dental and oral health. Surabaya City residents experience dental and oral health problems of 49.05% which are influenced by various characteristics of the mother. Therefore, this study aims to determine the role of maternal characteristics that influence cases of Maternal dental anxiety during the Covid-19 pandemic in the city of Surabaya. Method cross-sectional analytic research with sampling technique using convenience sampling and data analysis was performed using a regression test. Result the characteristics of the mother, namely the husband's occupation and household income, proved to affect maternal dental anxiety, with p-values of 0.008 and 0.005. The most dominant factor in Maternal dental anxiety is household income with a percentage of 50.6%. Conclusion there is a role for the characteristics of the mother that influences the case of maternal dental anxiety.